2014
DOI: 10.1186/1756-0500-7-463
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of carers on medication management in dementia: lessons from collaboratively developing a research proposal

Abstract: BackgroundThe need for carers to manage medication-related problems for people with dementia living in the community raises dilemmas, which can be identified by carers and people with dementia as key issues for developing carer-relevant research projects.A research planning Public Patient Involvement (PPI) workshop using adapted focus group methodology was held at the Alzheimer’s Society’s national office, involving carers of people with dementia who were current members of the Alzheimer’s Society Research Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(110 citation statements)
references
References 13 publications
4
102
1
3
Order By: Relevance
“…However, health-care systems and structures were often not helpful, for example family caregivers might not be included in communications about medication regimen changes and were not given the information and support that they needed to carry out their medication management roles. A focus group with carers of PLWD 148 found that carers felt unsupported by health and social care teams in terms of dealing with the practicalities of medication administration. There were also issues around the difficulties of recognising when a PLWD was no longer able to safely administer medication and ambiguity about where responsibility should lie for monitoring their use of medication.…”
Section: Views and Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, health-care systems and structures were often not helpful, for example family caregivers might not be included in communications about medication regimen changes and were not given the information and support that they needed to carry out their medication management roles. A focus group with carers of PLWD 148 found that carers felt unsupported by health and social care teams in terms of dealing with the practicalities of medication administration. There were also issues around the difficulties of recognising when a PLWD was no longer able to safely administer medication and ambiguity about where responsibility should lie for monitoring their use of medication.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…Seven 72,92,102,125,132,148,162 were qualitative studies, one 107 was a mixed study including a review and a qualitative study, three 93,99,153 were reviews and two 20,94 were questionnaire studies. Three studies 20,94,102 focused on people with dementia and diabetes, two 72,93 focused on those with dementia and VI, one 89 looked at those with dementia and deafness, one 92 focused on those with dementia and cancer, two 148,153 looked at family carers' views on medication management and four 99,107,125,132 looked at the needs of people with dementia in general hospitals. Literature on the experiences of older people with dementia in acute general hospitals has highlighted shortcomings in the care provided, the attitudes and training of staff, and the physical environment and problems with care cultures.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…Having an informant for each participant would also be useful to ensure that, if the intervention is pharmacological, it is taken in adherence with the protocol, as medication management can be difficult for people with dementia, and often caregivers provide support. 479,480 Informants are also often involved in the completion of outcomes on behalf of the person with dementia they care for. There was discussion around who completes outcomes at both the PPI consultation and consensus conference and, although it is important that people with dementia should be enabled to complete measures, informal carers also need to be involved.…”
Section: Recommendations Around Completing Outcomesmentioning
confidence: 99%
“…A hozzátartozók hangsúlyos szerepét a demenciával élők ellátásában jelen kutatás eredménye is megmutatta. A családtagokat a gondozói szerepben érő pozitív és negatív hatások aktívan kutatott terület, és a többségében kvantitatív módszertan mellett már kvalitatív metódusok is feltűnnek (Poland et al, 2014). A részvételnek mint mód-szertannak ilyen jellegű kutatásban történő alkalmazása mindenképpen megfontolandó következő lépésként, és a gondozó hozzátartozók mellett akár a demencia kezdeti stádiumában lévő érintettek bevonása sem irreális cél.…”
Section: Következtetésekunclassified